2009
DOI: 10.1016/j.atherosclerosis.2009.01.040
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR metabonomics can differentiate the early atherogenic effect of dairy products in hyperlipidemic hamsters

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Page 1 of 18A c c e p t e d M a n u s c r i p t D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 44 publications
2
38
0
1
Order By: Relevance
“…Also, neither raw nor retrograded resistant starch had any significant effect on the serum lipids of healthy subjects [15]. Martin et al [23] indicated that the determinal effect of a high saturated intake on atherogenesis can be modulated by accompanying compounds or the physico-chemical nature of the food matrix. This may be considered as another factor responsible for the observed differences in the atherogenic effects of the different processed cheeses tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, neither raw nor retrograded resistant starch had any significant effect on the serum lipids of healthy subjects [15]. Martin et al [23] indicated that the determinal effect of a high saturated intake on atherogenesis can be modulated by accompanying compounds or the physico-chemical nature of the food matrix. This may be considered as another factor responsible for the observed differences in the atherogenic effects of the different processed cheeses tested.…”
Section: Discussionmentioning
confidence: 99%
“…The long chain ω-3 fatty acids are known by their protective effect on the CVD [26]. Recently, a study based on conventional and metabonomic approaches showed that the lowest atherogenicity was obtained with canola cheese diet followed by the dairy fat cheese diet, while the greatest atherogenicity was observed with the butter diet (P < 0.05) in hyperlipidemic hamsters [23]. Also, in the controlled dietary study on human subjects [3,29], cheese was less cholesterol increasing than butter at equal fat content.…”
Section: Introductionmentioning
confidence: 99%
“…Exclusion criteria were as follows: a history of head injury with a loss of consciousness .30 min; a substantial physical (e.g., uncorrected visual impairment or hemiparesis), neurologic (e.g., seizure disorder), or psychiatric (e.g., active psychosis) disability that precluded involvement in the study; evidence of any other known causes of mental deficiency (e.g., congenital hypothyroidism, neurofibromatosis, or chromosomal abnormalities); or the prescription of medications that were suggestive of or might increase risk of atherosclerosis (e.g., b blockers, hormone supplements, protease inhibitors, and long-term systemic prednisone and cyclosporine) because of a remote associative risk of choline metabolite trimethylamine-N-oxide with atherosclerotic heart disease in cardiac patients (20)(21)(22)(23)(24). Medication changes during the treatment period did not preclude study participation but were monitored.…”
Section: Participantsmentioning
confidence: 99%
“…The model that maximized the explained variance (R 2 ) and predicted variance (Q 2 ) and validated the following crossvalidation ANOVA was selected. See Supplementary Methods under "Supplemental data" in the online issue for additional validation procedures of PLS regression models (41,42) that were also performed. SIMCA-P12 software (Umetrics) was used for all multivariate data analyses and modeling.…”
Section: Statistics: Pls Regressionmentioning
confidence: 99%